Relaxation and conduction mechanism of BNT-KNN ceramics by impedance study. (10th September 2017) - Chandrasekhar, M.; Kumar, P.; Prakash, C.; Kumar, Anil
ABSTRACT: Impedance spectra of 0.93BNT-0.07KNN revealed positive and negative temperature coefficient of resistance behaviour up to 400 °C and above 400 °C . With the increase of temperature, decreased radii and displaced centres of semicircles from the real axis of impedance Cole-Cole plots suggested non-Debye type relaxation mechanism. Three dielectric relaxation regions: within (i) grain, (ii) grain- grain boundary and (iii) grain boundary were prominent in lower, middle and high temperature regions, respectively. The activation energy ranging from ∼0.79 to 1.2 eV, suggested that the conduction carriers were cation and cation, oxygen vacancies in lower and higher temperature regions, respectively.